Factor biosociodemográficos y calidad de vida de los pacientes en Hemodiális en Clínica de Trujillo - Liñan Nizama, Lourdes Katherine (2015)
This study is quantitative research, correlational, descriptive cross-sectional, was conducted in patients of a hemodialysis unit Clinic Trujillo La Libertad; in order to determine the demographic factors, and quality of life. The sample consisted of 40 patients, which were selected according to the inclusion and exclusion criteria. Instruments was used to measure the quality of life of patients on hemodialysis by physical, emotional, social, personal relationships and rental. The reliability of the instrument was determined by the statistical test of Cronbach Alpha. Sociodemographic factors taken in this research study, it was identified that the stage of life that prevails is that of mature adults 65 percent, males 55 percent, the degree of secondary education with 35 percent, time of disease 1-4 years 75 percent, and unoccupied patient with 45 percent. was shown that biosociodemographic factors social role and level of education if they are related to quality of life in hemodialysis patients with validated statistical test Chi Square of 15,014 and 24,812 respectively. Biosociodemographic factors: age, sex and disease duration, unrelated to the quality of life in patients hemodialysis. 40 percent of hemodialysis patients have a good quality of life, followed by 37.5 percent and 22.5 percent regular poor quality life.